Capital Budgeting Strategy of Power Plant for Internal Use: Case Study of Coal Fired Steam Power Plant (CFSPP/PLTU) 2X55 MW PT. Bosowa Maros Energi for PT. Semen Bosowa Maros in Kabupaten Maros, South Sulawesi - Faremi Adirama, Farza; Sumirat, Erman (The Indonesian Journal of Business Administration, 2017)
Abstract. This paper discusses the Power Plant financing scheme for PT. Bosowa Maros Energy (BME) to be undertaken by PT. Semen Bosowa Maros (SBM). This power plant will be used to support the performance of PT. SBM in the future, as today machine utilization of PT. SBM is currently still below 50%, due to PT. SBM recent investment on Bosowa Cement Line-Unit II. In the future, with the operating Cement Line-II, production capacity of Semen Bosowa Maros will reach 85 percent of its capacity (on average) or equivalent to 85 MW of electricity use. Power Plant to be built will use Steam Power Plant (PLTU) system. All aspects of PLTU must be prepared, including selection of location, technical specification and machine, coal requirement, and so on. Legal and environmental aspects also need to be studied so as not to disturb with aspects of community life and Indonesian Law. Finally, the financial aspect must be calculated carefully so that the return of this investment can run well within the specified time period. The feasibility study of this paper is feasible according to the financial calculation, either by NPV, IRR, or Pay Back Period (PBP) parameters, so we can expect the development continue.Keywords: Feasibility Study, Electricity, Steam Power Plant (PLTU), PT. Semen Bosowa Maros (SBM), PT. Bosowa Maros Energy (BME)